Strategic management at the beginning of the XXI century : the impact of crisis turbulences - Polowczyk, Jan (Economics and Business Review, 2012)
The nature of corporate strategy problems cannot easily be framed within a fixed paradigm. Strategic management is necessarily a multi-paradigmatic discipline, requiring varied theoretical perspectives and methodologies. The purpose of this paper is to present and assess the evolution of corporate strategic management in the first decade of the current century, particularly under the influence of the recent economic crisis. For the last two decades strategic management has been dominated by a resource-based view. Recently we can distinguish two important perspectives of research: behavioral and institutional. The first regards decision-making processes of company executives based on considerable progress made by psychologists in identifying and validating fundamental cognitive constructs which are promising for advancing theory and research on top management teams. The institutional perspective is based on increased realization of the importance of national and global institutions for the competitiveness of companies, sectors and countries. (original abstract)